Facade of BMC building with coat-of-arms - Ghosh, Ayan (2023)
Sir Bartle Henry Frere, governor of Bombay Presidency between 1862–67, demolished the ramparts of Fort George to allow Bombay to expand beyond the fort walls. As the city limits expanded, there was need for a municipality to overlook the civic infrastructure development of the suburbs. Accordingly, the Municipal Corporation of Greater Mumbai was created in 1865, and Arthur Crawford was appointed the first municipal commissioner.